2021
DOI: 10.1111/jcmm.16618
|View full text |Cite
|
Sign up to set email alerts
|

The role of SIRT2 in vascular‐related and heart‐related diseases: A review

Abstract: Cardiovascular diseases have become one of the important factors that endanger human health, and post-translational modifications of related proteins play an important role in this. [1][2][3][4][5] Among them, acetylation and deacetylation have increasingly become the focus of research. The seven-member sirtuins family (SIRT1-7) belongs to the third deacetylase. In order to catalyse the deacetylation reaction, this protein requires the presence of nicotinamide adenine dinucleotide (NAD + ) to have deacetylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…In this research, we found that IBC-induced S-phase arrest of the breast cancer cells cycle was abrogated by the antioxidant NAC, indicating that the inhibitory effects of IBC on breast cancer cells are ROS-dependent. Studies show that SIRT2 can reduce ROS levels, which is a novel strategy for the treatment of diabetic cardiomyopathy (Wu et al, 2021). In addition, another study showed that the SIRT2 inhibitor TM significantly increased ROS levels in cholangiocarcinoma cells (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we found that IBC-induced S-phase arrest of the breast cancer cells cycle was abrogated by the antioxidant NAC, indicating that the inhibitory effects of IBC on breast cancer cells are ROS-dependent. Studies show that SIRT2 can reduce ROS levels, which is a novel strategy for the treatment of diabetic cardiomyopathy (Wu et al, 2021). In addition, another study showed that the SIRT2 inhibitor TM significantly increased ROS levels in cholangiocarcinoma cells (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sirt2 is an NAD+-dependent deacetylase that is widely involved in cell division, angiogenesis [48][49][50] , energy metabolism [51] and neurodegenerative [52,53] , cardiovascular disease [54,55] , oxidative stress [56] and many cancers [57,58] , etc. Studies have found that Sirt2 was the most abundant sirtuin expressed in mammalian CNS, especially in cortex, striatum, hippocampus, and spinal cord, suggesting that it might have a role in CNS [59] .…”
Section: Discussionmentioning
confidence: 99%
“…[57] Additionally, SIRT2 plays a crucial role in vascular diseases, with its effects on endothelial cell damage dependent on the degree of oxidative stress. [58] Yu et al [59] found that the mRNA and protein levels of SIRT2 were increased in rat cardiomyocytes after short-term CR. Notably, in aortic smooth muscle cells treated with resveratrol, a compound that mimics the effects of CR, SIRT1, SIRT3, and SIRT4 expression was upregulated, while SIRT6 was downregulated, and SIRT2 expression remained unaltered.…”
Section: Potential Mechanisms Linking Cr Cvds and Sirtuinsmentioning
confidence: 99%